1997
DOI: 10.1063/1.869481
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of dense bubble suspensions

Abstract: Flow of artificial microcapsules in microfluidic channels: A method for determining the elastic properties of the membrane Phys. Fluids 20, 123102 (2008) On the rest state stability of an objective fractional derivative viscoelastic fluid model J. Math. Phys. 49, 043101 (2008) Effect of surface hydrophilicity on the confined water film Appl. Phys. Lett. 91, 253110 (2007) Rheology and ultrasonic properties of Pt57.5Ni5.3Cu14.7P22.5 liquid Appl. Phys. Lett. 90, 171923 (2007) The rheological behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
0
35
2
Order By: Relevance
“…Preliminary results in that direction have already been obtained for massless bubbles (Yurkovetsky & Brady 1996;Khang et al 1997;Spelt & Sangani 1998) but they must be extended to massive particles in a form which satisfies the energy conservation condition (2.5) before considering the hyperbolicity issue.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results in that direction have already been obtained for massless bubbles (Yurkovetsky & Brady 1996;Khang et al 1997;Spelt & Sangani 1998) but they must be extended to massive particles in a form which satisfies the energy conservation condition (2.5) before considering the hyperbolicity issue.…”
Section: Discussionmentioning
confidence: 99%
“…For the case of a bubble suspension in which the Reynolds number is large and the Weber number is small, a complete set of governing equations can be composed from first principles. 1,2 The extent of the validity of these theories could only be assessed if comparisons with detailed experimental measurements are performed. Hence, there is a need for accurate measurements of velocity and concentration profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The neglect of hydrodynamic interactions is a reasonable approximation when the relative velocity of interacting bubbles is large compared with their common velocity. For example, Kang et al 9 found that for sheared bubble suspensions without buoyancy, hard-sphere simulations were in close agreement with simulations of hydrodynamically interacting bubbles. Likewise, Kumaran and Koch 13 found that buoyant bubbles with different terminal velocities would encounter and separate in a manner qualitatively similar to a hard-sphere bounce ͑although the bubbles did not make actual contact͒ when the difference of velocities was larger than about 10% of the mean velocity.…”
Section: Introductionmentioning
confidence: 63%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] In particular, the special case of flows in which the hydrodynamic interactions among bubbles can be determined using the potential flow approximation has been extensively studied. [8][9][10]13,15 The potential flow approximation is expected to be valid when the Reynolds number based on the bubble radius and characteristic velocity is large compared with unity but the Weber number, the ratio of inertial to surface tension forces, is small enough so that the bubbles are approximately spherical, and the liquid is free of surface-active impurity. [16][17][18][19][20] This somewhat ideal case can be studied experimentally, 21,22 numerically using large scale simulations which account for the hydrodynamic interactions among bubbles, 15 and analytically using the methods of statistical mechanics 23 and kinetic theory of dense granular materials.…”
Section: Introductionmentioning
confidence: 99%